Design and Implementation of a Self-Starting Permanent Magnet Hysteresis Synchronous Motor for Pump Applications - Gedikpinar, Mehmet (Ieee-Inst Electrical Electronics Engineers Inc, 2019)
A Permanent Magnet Hysteresis Synchronous Motor (PMHSM) is designed and implemented in this paper. The designed motor is analyzed by using simulation and experimental studies. The torque, torque ripple, speed and flux density are also analyzed by using Finite Element Analysis (FEA) method. A standard commercial stator geometry is preferred for easy installation. A new rotor structure is designed for the motor. A submersible pump turbine is connected to the prototype motor in order to test under a real pump load condition by a pump test stand. The same pump used in the experiment was also tested with a commercial induction motor (IM) submersible pump motor with same power. Thus, the commercial and proposed motor are compared in terms of static head value, which is an important value in pump applications. The performance of the motor is better than the IM because it can operate at synchronous speed without slip. In addition, the proposed motor does not require any auxiliary system to achieve starting with grid. The proposed PMHSM can be used to obtain high performance and efficiency for pump applications.
Keywords: AC machine; hysteresis motor; permanent magnet motor; pump; hybrid rotor